Optimization of Maxillary Obturator Thickness Using a Double-Processing Technique - Won-suck Oh, DDS, MS1 & Eleni D. Roumanas, DDS2 (Journal of Prosthodontics, 2008)
Preservation of remaining structures is a primary goal of prosthetic rehabilitation. Continuously applied stresses on the remaining tissues from a large, heavy obturator jeopardize the health of the tissues, compromise the function of the prosthesis, and affect patient comfort